2018
DOI: 10.3389/fpsyg.2018.01532
|View full text |Cite
|
Sign up to set email alerts
|

The Power of EI Competencies Over Intelligence and Individual Performance: A Task-Dependent Model

Abstract: Prior research on emotional intelligence (EI) has highlighted the use of incremental models that assume EI and general intelligence (or g) make independent contributions to performance. Questioning this assumption, we study EI's moderation power over the relationship between g and individual performance, by designing and testing a task-dependent interaction model. Reconciling divergent findings in previous studies, we propose that whenever social tasks are at stake, g has a greater effect on performance as EI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 94 publications
0
6
0
1
Order By: Relevance
“…The results of structural modeling show that a central task for hotel managers is explaining the impact of employees' aesthetic labor on managers' emotions and social skills. Empirical research has shown that ESC improves work performance (Boyatzis and Goleman, 2007;Boyatzis et al, 2012;Truninger et al, 2018) and that the relationship between job performance and emotional and social competences should be more thoroughly examined (Boyatzis et al, 2015). Aesthetic labor is a new factor being considered in tourism.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of structural modeling show that a central task for hotel managers is explaining the impact of employees' aesthetic labor on managers' emotions and social skills. Empirical research has shown that ESC improves work performance (Boyatzis and Goleman, 2007;Boyatzis et al, 2012;Truninger et al, 2018) and that the relationship between job performance and emotional and social competences should be more thoroughly examined (Boyatzis et al, 2015). Aesthetic labor is a new factor being considered in tourism.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…It explains the relationship between managers' ESC and the social psychological environment for aesthetic labor. SET indicates that if a good exchange relationship is developed between employees and managers, drawing on their ESC, employees display better aesthetic performance due to mutual trust (Truninger et al, 2018).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…The studied SLP is a voluntary and transversal program in graduate studies open to all students at the master's level of a business school in the city of Barcelona. The program aims to complement the specific training received in the regular subjects of each degree, starting with becoming aware and strategically mobilizing EC, fostering a space for combining reason and emotion (Alburquerque et al, 2018) for self-leadership.…”
Section: The Self-leadership Programmentioning
confidence: 99%
“…The collection of data from self-reported sources presents a possible internal bias component, even for the protagonist participants themselves, along with the possibility of being conditioned by their attitudes and motivations (Bar-On, 1997 cited in Alburquerque et al, 2018).…”
Section: Limitationsmentioning
confidence: 99%
“…These are intellectual or cognitive abilities, self-management or intrapersonal abilities, and relationship management or interpersonal abilities. The latter two groups of competencies are considered part of the emotional intelligence proficiencies (Boyatzis et al, 1999;Kővári, 2016;and Truninger et al, 2018).…”
Section: Introductionmentioning
confidence: 99%